Networked collaboration: towards a definition of online collaborative learning - Montse Guitert; María Pérez-Mateo (Ediciones Universidad de Salamanca, 2013)
<!--[if gte mso 9]> 0 0 1 62 346 USAL 2 1 407 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P